Impact of Combined Acidic and Hyperosmotic Shock Conditions on the Proteome of Listeria monocytogenes ATCC 19115 in a Time-Course Study - Dong Lai Zhang; Ya Long Bai; John P. Bowman (Journal of Food Quality)
Listeria monocytogenes can cause listeriosis in humans through consumption of contaminated food and can adapt to and grow under a wide array of physiochemical stresses. Consequently, it causes persistent food safety issues and requires vigilant sanitation processes to be in place, especially for the manufacture of high-risk food products. In this study, the global proteomic responses of the food-borne pathogen L. monocytogenes strain ATCC 19115 were determined when exposed to nonthermal inactivation. This process was examined in the early stationary growth phase with the strain placed under simultaneous exposure to low pH (pH 3.5) and high salinity (aw 0.900, 14% NaCl). Proteomic responses, measured using iTRAQ techniques, were conducted over a time course (5 min, 30 min, and 1 h at 25°C). The enumeration results showed that, at 5 min, cells underwent initial rapid inactivation by 1.2 log units and 2.5 log units after 30 min, and after that, culturability remained stable when sampled at 1 h. From the iTRAQ results, the proteome level changes that occur rapidly during the inactivation process mainly affected prophage, cell defense/detoxification, carbohydrate-related metabolism, transporter proteins, phosphotransferase systems, cell wall biogenesis, and specific cell surface proteins. Pathway map analysis revealed that several pathways are affected including pentose and glucuronate interconversions, glycolysis/gluconeogenesis, pyruvate metabolism, valine, leucine and isoleucine biosynthesis, oxidative phosphorylation, and proteins associated with bacterial invasion of epithelial cells and host survival. Proteome profiling provided a better understanding of the physiological responses of this pathogen to adapt to lethal nonthermal environments and indicates the need to improve food processing and storage methods, especially for non- or minimally thermally processed foods.